A mini-review of the role of condensin in human nervous system diseases - Pang, Du; Yu, Shengping; Yang, Xuejun (Frontiers in Molecular Neuroscience, 2022)
Mitosis and meiosis are crucial life activities that transmit eukaryotic genetic information to progeny in a stable and orderly manner. The formation and appearance of chromosomes,which are derived from chromatin,are the preconditions and signs of mitosis.When entering mitosis, interphase loose chromatin is highly spiralized and folded to form compact chromosomes. In recent years, it has been found that in addition to the well-known DNA, histones and topoisomerase, a large protein complex called condensin plays an important role in the process of chromosomes formation. Numerous studies have shown that the abnormal function of condensin can lead to incomplete or excessive concentration of chromatin, as well as disorder of genome organization process, abnormal transmission of genetic information, and ultimately lead to various diseases of individual, especially in nervous system diseases. In this review,the biological function of condensin and the potential pathogenic mechanism of condensin in nervous system diseases are briefly summarized. Therefore, the investigation of these mechanisms makes a significant contribution to the understanding of those related diseases and provides new ideas for clinical treatments.